Association of physical activity, sedentary behavior and stroke in older adults - Bai, Long; Wen, Zongliang; Yan, Xuebing; Wu, Shenqin; Chen, Jialin (Frontiers in Public Health, 2024)
ObjectiveThe aim of this study was to investigate the relationship between physical activity, sedentary behavior and stroke in people aged 60 years and older.MethodsThe study included 3,010 participants aged 60 and older from the National Health and Nutrition Examination Survey (NHANES). Data on sedentary behavior, physical activity and stroke were obtained through questionnaires. Statistical analyses were performed using a complex multistage sampling design and weighted multivariate logistic regression. Smoothed curve fitting and threshold effects analyses were used to explore non-linear relationships between physical activity, sedentary behavior and stroke.ResultsThere were 244 (7.53%) participants aged 60 years and older who had experienced a stroke. After adjusting for all covariates, physical activity, sedentary behavior and stroke were significantly associated [OR (95% CI) for physical activity: 0.622 (0.443, 0.875), p = 0.009; OR (95% CI) for sedentary behavior: 2.602 (1.557, 4.348), p = 0.003]. C-reactive protein mediated the association between sedentary behavior and stroke among older adults, with a mediation of 3.64%.ConclusionIn people aged 60 years and older, sedentary behavior was positively associated with stroke, whereas physical activity was negatively associated with stroke, and C-reactive protein mediated the relationship between sedentary behavior and stroke.